The Study of the Cycle of Packaged Tours from the Primorsky Territory - Martyshenko, Natalya Stepanovna; Kmet, Elena Borisovna; Kim, Angelina Georgievna (International Journal of Economics and Financial Issues, 2015)
The concept of tourism development of most Russian cities and regions is based on the availability of the offer of certain tourism products and resources rather than on the analysis of the demand of the potential tourists. The article discusses the methodological approach to the study of the process of the tourist product consumption based on the five-step service marketing model. In accordance with the five-step service marketing model tourists’ negative memories of tours are essential for the development of a competitive tourism product. The negative reaction is generally studied by the use of questionnaires with open questions. For conducting a quantitative analysis of the statements information structuring by determination of the typology of respondents’ responses is previously performed. Our study demonstrates the possibility of using such tool as the typology of consumers when creating a competitive tourism product in the region. The proposed approach proves the need for continuous monitoring of the structure of the consumer cycles in various types of tourism. The article provides the results of the study of consumers’ negative impressions after the consumption of the most common types of tourist services in the Primorsky Territory. The presented conclusions are based on large-scale observations of the Primorsky Territory tourists conducted for more than ten years. Keywords: tourism, consumer typology, questionnaire, the marketing consumption model. JEL Classifications: Z31, Z32, Z38